Determinan yang Mempengaruhi Pembiayaan Murabahah Pada Perbankan Syariah di Indonesia - Herni Ali; Miftahurrohman Miftahurrohman (Faculty of Economic and Business, 2016)
Determinants of Murabahah Financing in The Indonesian Islamic Banking IndustryThe purpose of this research is to analyze the influence of the Third Party Funds (DPK), Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Return on Asset (ROA), Operational Efficiency Ratio (BOPO), Inflation, Credit Interest Rate and Gross Domestic Product (GDP) to volume of Murabahah financing in sharia banking. The analysis method used is multiple linier regressions. The result of this study shows that: Third Party Funds (DPK), Return on Assets (ROA), Inflation and GDP are positively influence to Murabahah Financing. For Capital Adequacy Ratio (CAR) and Credit Interest Rate is partially significant negative influence to Murabahah Financing. While NPF and BOPO does not influence to Murabahah FinancingDOI: 10.15408/ess.v6i1.3119